Remarkable Harmony in Diversity: Religious Moderation through the Gemohing Lamaholot Tradition at Watanhura East Flores Indonesia - Yosep Belen Keban; Benedikta Yosefina Kebingin; Maria Inviolata Deran Ola (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Religious moderation has not had a special place in the hearts of Indonesian people since the government promulgated it. Many religious issues or conflicts are shown or occur in the homeland. Thus, a movement is needed to campaign intensely for religious moderation through the local wisdom embodied by local communities like the Gemohing tradition in the Lamaholot tribe. The study aimed to identify the tradition of Lamaholot as a local wisdom that can strengthen religious moderation in the village of Watanhura-Flores East. The method used in this study is ethnography with a qualitative approach, which was carried out in October-November 2023. This research data is known from observations and interviews with 12 sources from the village of Watanhura. The results that will be expected in this study are that the Gemohing Lamaholot tradition that is lived by the community of the East Watanhira-Flores can be a reference for uniting or strengthening religious moderation in the East in particular and in Indonesia in general. For that, the heirs of the cultural values of Lamaholot, in particular in the village of Watanhura, can make or preserve this local culture as local wisdom in building and strengthening religious moderation in living together amidst tribal, cultural, racial, and religious differences.